Reformasi Hukum di Indonesia dari KUHP Kolonial ke KUHP Modern, Tantangan dan Prospeknya - Yunita, Nita; Herawati, Herawati; Darmana, Maman Dana; Ratnawati, Endah; Witandri, Witandri; Candra, Firman Adi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This article analyzes the transition from the colonial-era Indonesian Penal Code (KUHP) inherited from Dutch rule to the modern KUHP enacted in 2023 and effective from 2026, focusing on the shift from retributive justice to restorative principles. The colonial KUHP, based on the 1918 Wetboek van Strafrecht, emphasized imprisonment and state control, often clashing with Indonesian values and social realities. In contrast, the new KUHP incorporates human rights, alternative sanctions like community service, and recognition of customary laws, marking a historic break from colonial legacy. Key challenges include potential curbs on civil liberties through provisions on insults to state officials (e.g., Pasal 240-241), implementation gaps in harmonizing subordinate regulations, and balancing cultural norms with global standards. Prospects lie in enhanced victim protection, corporate accountability, and alignment with international trends, though success depends on judicial review by the Constitutional Court and public education. This reform represents a progressive step toward a more inclusive and equitable criminal justice system in Indonesia.